Ultimate Load Tests on Bearing Behavior of Large-Diameter Bored Piles in Weathered Rock Foundation - Xiaoyu Bai; Xueying Liu; Mingyi Zhang; Yonghong Wang; Nan Yan (Advances in Civil Engineering)
Based on the vertical compressive static load test and pile mechanics test of three large diameter bored piles (one of the test piles was treated with postgrouting) in granite gneisses foundation, the bearing capacity, deformation characteristics, and influencing factors of the single pile under the limit state are analyzed and compared with the recommended values of survey report and the recommended values of current codes. By comparing the measured and theoretical values of pile axial force, the bearing capacity of cast-in-place pile under normal and limit conditions is analyzed. The experimental results show that the Q-s curve of large-diameter rock-socketed mud wall retaining bored pile with a length-diameter ratio of 25–33 and rock-socketed depth of 5–8 d shows a rapid growth. After grouting treatment, the ultimate compressive bearing capacity of single pile is improved, the maximum settlement is reduced by 6.6%, the rebound rate is reduced by 11.1%, and the settlement effect of controlling pile top is not significant. The bearing capacity and deformation characteristics of the three test piles are less affected by length-diameter ratio and rock-socketed depth. For postgrouting piles, the ratio of frictional resistance of rock-socketed segment and the ratio of pile lateral resistance are less affected by length-diameter ratio and rock-socketed depth, while, for postgrouting piles, the ratio of pile lateral resistance is more affected by rock-socketed depth. The pile end resistance ratio of the three test piles is significantly affected by the rock-socketed depth, whether or not the pile side postgrouting treatment is carried out.